2020
DOI: 10.1097/mrr.0000000000000407
|View full text |Cite
|
Sign up to set email alerts
|

The dose of robot-assisted gait therapy may influence functional recovery in a multidisciplinary rehabilitation program: an exploratory retrospective study

Abstract: Robot-assisted gait training (RAGT) has been introduced in clinical practice to increase training intensity in patients with neurological disorders. In this observational study, we investigated the effect of the number of RAGT sessions on functional recovery in a heterogeneous cohort of patients. We included patients with a diagnosis of gait impairment due to a neurological disease. A set of demographic, clinical, functional and training parameters was collected for each participant. Each patient received RAGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…Similarly, we found higher functional gains in patients that received RAGT earlier (within 6 weeks). Indeed, a specific time window for spontaneous recovery exists, that can be set within the first 6–12 weeks for gait recovery [22,43,44] when gait robotics are recommended to optimise functional gains [17]. Indeed, a recent update of the Cochrane review has stated that people in the first 3 months after stroke and those who are not able to walk, seem to benefit most from electromechanical-assisted gait training in combination with physiotherapy [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, we found higher functional gains in patients that received RAGT earlier (within 6 weeks). Indeed, a specific time window for spontaneous recovery exists, that can be set within the first 6–12 weeks for gait recovery [22,43,44] when gait robotics are recommended to optimise functional gains [17]. Indeed, a recent update of the Cochrane review has stated that people in the first 3 months after stroke and those who are not able to walk, seem to benefit most from electromechanical-assisted gait training in combination with physiotherapy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Even though intensity, measured as time spent in rehabilitation activities, seems to be relevant for optimising functional recovery [1,16], scarce evidence is available on the role of robot-assisted gait training (RAGT) dose for functional outcomes. Recently, it has been hypothesised that the dose of RAGT may influence functional recovery in patients who have undergone a multidisciplinary program [17]. The aim of this pragmatic observational study was to identify the optimal dose and timing of RAGT that can lead to a favourable outcome in a sample of subacute stroke survivors.…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantial amount of literature concerning the efficacy of TAT and the importance of the therapy dosage in the rehabilitation of stroke patients [ 23 , 52 , 53 ]. Our data confirm these previous results.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies over the last few decades have shown the effectiveness and the advantages of using robotic systems for neurorehabilitation (45,46,47) and tele-rehabilitation in last decades (48,49,50).…”
Section: Discussionmentioning
confidence: 99%